Basic training requirements for teachers from the viewpoint of supervisors in Mafraq Governorate (Journal of the College of Education for Women, 2019)
This study aimed to reveal the stage for teachers of basic training needs from the perspective of workers in Mafraq Governorate, through a survey of a sample of counselors look at the Ajloun area schools reached (58) counselors.To achieve the objective of the study was constructed questionnaire where they are finalized (18) items distributed on two dimensions (professional needs, performance requirements) and after confirmation of the validity and reliability have been applied to the sample where the results showed that training needs were high, both on a professional or per formative level .The results also showed no statistically significant differences in the areas of tool due to gender, educational qualification. The study concluded that a set of recommendations.keywords: Training needs, teachers of the basic stage.